Uma perspectiva de resolução de problemas no ensino médio: - MENEZES, Jailson Resplandes de (Universidade Federal do Tocantins, 2023)
This work is a study that is concerned with the theoretical nature of the educational component called Problem Resolution. As research spectrum were analyzed articles published in the Annals of Mathematics Education National Meeting in the 2007 editions, 2010 and 2013. These analyzes are given through a qualitative literature review and included the establishment previous categories to find possible answers to the following question; in which aspects to Problem Resolution in high school can contribute to the development of students and teachers? Sixteen works were analyzed. The overall objective of the research was to identify the contribution of the use of problem resolution in high school for the development of students and teachers. Among the results is emphasized that Problem Resolution can contribute significantly to the development of the student beyond the understanding of mathematical content, to stimulate cooperation and social interaction, as for teachers, found guidance is in the sense that the same, develop review tools and expanding their teaching practices.